Comparison of the different supports used in veterinary medicine for pressure sore prevention. (31st July 2019) - Caraty, J.; De Vreught, L.; Cachon, T.; Moissonnier, P.; Bongartz, A.; Viguier, E.; Carozzo, C.
Abstract : Objectives: To compare the pressure‐relieving capacity of different supports used in veterinary medicine and to find the more common pressure sore locations in laterally recumbent dogs, so as to recommend protocols for decubitus ulcer prevention. Materials and Methods: We compared the support properties of: (1) blankets on the floor, (2) a standard mattress, (3) a veterinary memory foam mattress and (4) a human medicine memory foam mattress. Three cadaver dogs with different body condition scores but similar sizes were positioned on the different supports in lateral recumbency. Pressures were measured in each dog and at each support contact point over a 4‐hour period using a TexiSense pressure mat. Results: Regardless of the body condition score and the support used, the skin overlying the scapula‐humeral articulation, the greater trochanter and the thirteenth rib were the recurrent risk zones. In these risk zones, pressure‐relieving mats led to lower pressures than did the standard mats or the blanket placed on the floor. The contact pressures appeared to depend on body condition score, with maximal pressures observed in thin dogs. Clinical Significance: It is important to use a pressure‐relieving mat to reduce the risk of pressure sores, but static pressure‐relieving mats are generally insufficient to maintain safe pressures in risk zones (<60 mmHg), particularly in thin patients, and so frequent changes in position are recommended.